Pengaruh Bahan Baku Terhadap Karakteristik Sensoris dan Komposisi Kimia Pada Terasi Berbasis Udang Rebon (Mysis relicta) dan Ikan Teri (Stolephorus commersonii - Mulyati, Sri; Sukmawati, Nina; Roviati, Evi (Journal of Applied Agriculture, Health, and Technology, 2024)
Shrimp paste (terasi) is a traditional product made from fermented rebon shrimp or small fish with addedsalt, characterized by its unique aroma and flavor. Fermentation is breaking down complex compoundsin food into simpler ones, resulting in a product with a distinctive aroma and taste. The objective of thisstudy was to determine the better sensory and chemical properties of shrimp paste made from rebonshrimp and anchovies. This research employed a completely randomized design (CRD) method withtwo treatments: (F1; rebon shrimp and F2; anchovies), each weighing 250 grams. The observedparameters included color, aroma, taste, texture, and pH of the shrimp paste. The processing of shrimppaste involved grinding, drying, and fermenting for seven days. Sensory analysis results showed thatrebon shrimp paste (F1) was preferred, with sensory scores above 4, and exhibited bright red color,distinctive aroma, and savory taste. In contrast, anchovy shrimp paste (F2) was less preferred, withsensory scores below 4, and had a faded black color. The pH of both shrimp pastes was acidic, belowneutral pH (pH=7), due to lactic acid bacteria degrading compounds in the shrimp paste duringfermentation. The added salt contributed to extending the shelf life and enhancing the value of fisheryproducts.